A fermionic portal to a non-abelian dark sector - Belyaev, Alexander; Deandrea, Aldo; Moretti, Stefano; Panizzi, Luca; Ross, Douglas A.; Thongyoi, Nakorn (Frontiers in Physics, 2024)
We introduce a new class of renormalizable models for dark matter with a minimal particle content, consisting of a dark SU(2)D gauge sector connected to the standard model through a vector-like fermion mediator, not requiring a Higgs portal, in which a massive vector boson is the dark matter candidate. These models are labeled fermion portal vector dark matter (FPVDM). Multiple realizations are possible, depending on the properties of the vector-like partner and scalar potential. One example is discussed in detail. Fermion portal vector dark matter models have a large number of applications in collider and non-collider experiments, with their phenomenology depending on the mediator sector.